Practical Approaches to Securing an IT Environment - John C, Fuller; Cofie, Penrose; Warsame H, Ali; Emmanuel S., Kolawole (Communication and Network, 2017)
There are a number of IT Security journals available in the literature but none of these research papers have practically specified approaches to secure the IT environment at large. In this paper, more emphases will be laid on the practical ways to secure our IT environments and with some useful real-life scenarios. In today, securing our IT environment has become the key factor in the industry due to an increasing number of attackers invading and stealing the intellectual properties; thereby, rendering most IT industries to go out of businesses. They may find that understanding and translating IT security recommendations to implementable practices can be overwhelming. While this is a worthwhile and important task, there are also more practical ways to ensure you are using IT security best practices in your business. Therefore, the need to properly secure our IT environments in order to mitigate those attacks by using the right tools in all IT domains will be fully discussed in this research. This paper will focus more on protection of LAN-WAN Domain as a use case.
Keywords: Mitigation and Assessment; Intellectual Property; Attacks